Complete Freund's adjuvant–induced decrement of pruriceptor-mediated suppression of itch. (8th March 2021) - Yin, Wen; Liu, Li; Zhou, Yuxi; Zhang, Yunchun; Kong, Dexu; Xu, Saihong; Tang, Dan; Huang, Dan; Wen, Daxiang; Jiao, Yingfu; Fan, Yinghui; Gao, Po; et al.
Abstract: Peripheral inflammation is always accompanied by a noxious sensation, either pain or itch, providing a protective warning for the occurrence of pathological changes; however, the mechanisms determining whether pain, itch, or both will be elicited under certain inflammatory statuses are still far from clear. Complete Freund's adjuvant (CFA) contains heat killed and dried Mycobacterium tuberculosis widely used to induce inflammatory pain models, but how CFA treatment affects itch sensation and the possible mechanisms are still unclear. In this study, using itch behavior testing and calcium imaging, we showed that both the behaviors and calcium responses associated with Transient Receptor Potential Vanilloid 1 (TRPV1)-mediated histamine-dependent itch and Transient Receptor Potential Ankyrin 1 (TRPA1)-mediated histamine-independent itch were significantly suppressed by CFA treatment. Furthermore, to explore the possible cellular mechanisms, high-throughput single-cell RNA sequencing and real-time PCR were used to detect CFA-induced changes of itch-related genes in dorsal root ganglion (DRG) neurons. Our results revealed that although both nociceptive Trpv1 + and Trpa1 + DRG neurons were increased after CFA treatment, most known pruriceptors, including Hrh1 +, Mrgpra3 +, Mrgprd +, Htr3a +, Htr1f +, IL31ra +, Osmr +, and Lpar3 + DRG neurons, were significantly decreased, which may explain that CFA treatment caused itch suppression. This study indicated that itch sensation was affected after CFA treatment, although negatively, and comprehensive but not specific suppression of different pruriceptors was observed after CFA treatment, suggesting that a unified adaptive change of increased pain and decreased itch will occur simultaneously under CFA-induced inflammatory conditions.